Hydrogen‐Bonded Organic Framework Ultrathin Nanosheets for Efficient Visible‐Light Photocatalytic CO2 Reduction - Yu, Baoqiu; Meng, Ting; Ding, Xu; Liu, Xiaolin; Wang, Hailong; Chen, Baotong; Zheng, Tianyu; Li, Wen; Zeng, Qingdao; Jiang, Jianzhuang (Angewandte Chemie International Edition, 2022)
Post‐modification of robust guanine‐quadruplex‐linked 2,2′‐pyridine‐containing HOF‐25 with Ni(ClO4)2 ⋅ 6 H2O followed by exfoliation using sonication method affords hydrogen‐bonded organic framework (HOF) nanosheets (NSs) of HOF‐25‐Ni in the yield of 56 %. TEM and AFM technologies disclose the ultrathin nature of HOF‐25‐Ni NSs with thickness of 4.4 nm. STM observation determines the presence of sql segments assembled from HOF‐25‐Ni building blocks at the heptanoic acid/highly oriented pyrolytic graphite interface, supporting the simulated 2D supramolecular framework. ICP‐MS, XAS, and XPS data prove the successful immobilization of atomic nickel sites on the 20 % total 2,2′‐pyridine moieties in crystalline HOF‐25‐Ni. With the aid of [Ru(bpy)3]2+ and triisopropanolamine, 10 wt% HOF‐25‐Ni NSs dispersed on graphene oxide efficiently promotes visible‐light‐driven CO2 reduction, showing a 96.3 % CO selectivity with a prominent conversion rate up to 24 323 μmol g−1 h−1. Hydrogen‐bonded organic framework (HOF) nanosheets (NSs) of HOF‐25‐Ni have been produced by the post‐modification of robust guanine‐quadruplex‐linked metal‐free 2,2′‐pyridine‐containing HOF‐25 followed by exfoliation. With the help of a sensitizer, 10 wt% HOF‐25‐Ni NSs dispersed on graphene oxide promoted efficient and selective CO2‐to‐CO conversion under visible‐light irradiation.